(untitled) (Archive of Conferences, 2021)
One of the most common causes of damage to the visual analyzer at various levels is fractures of the orbit in cranio-orbital lesions (COL), including in combination with traumatic brain injury (TBI). In the structure of traumatic brain injury (TBI), COL accounts for 6-7%, and all types of combined TBI - 34%. Patients need the care of several neurosurgeons, ophthalmologists, otorhinolaryngologists, and maxillofacial surgeons. The consequences of eye injuries are the main cause of disability. Untimely and incorrect treatment of COI can lead to functional disorders of the organ of vision, cosmetic defects and purulent-septic complications.